Enhancing Employee Performance: Exploring the Impact of Work Environment and Work Discipline at the Karawang District Agriculture Office - Maydah, Sinta Rhaudatul; Jamaludin, Asep; Nandang, Nandang (Lembaga Riset dan Inovasi Al-Matani, 2024)
This study aims to determine, analyze and explain: (1) work environment; (2) work discipline; (3) employee performance; (4) partial effect of work environment on employee performance; (5) partial effect of work discipline on employee performance, and (6) simultaneous effect of work environment and work discipline on employee performance at the Karawang Regency Agriculture Office. The research was conducted using descriptive quantitative and verification methods, namely through literature studies conducted by studying the literature related to the research topic, as well as field studies conducted through interviews and direct observation to get an overview of the situation and conditions of the research site. The sample used was 90 respondents. Based on the results of the overall analysis, the research results are obtained, namely 1. The condition of the work environment is quite good. 2. Work discipline conditions are quite good. 3. Employee performance conditions are quite good. 4.The work environment partially affects employee performance 5.Work discipline partially has no effect on employee performance 6.The work environment and work discipline simultaneously affect employee performance at the Karawang Regency Agriculture Office.